Trends in Kaposi Sarcoma at the Charlotte Maxeke Johannesburg Academic Hospital after the antiretroviral drugs rollout in 2004 (from December 2004 to December 2019) - Hute, Fortune (My University, 2021)
Background: Kaposi sarcoma (KS) is anangioproliferative cancer of endothelial cells secondary to HHV8. It is classified as one of the most common presenting signs of AIDS during the HIV epidemic. Since HAART introduction in 1996, a worldwide reduction of AIDS associated KS was observed especially in developed countries. Factors influencing this improvement include compliance, effective treatment regimens and health conscious social circumstances. Objectives: To illustrate the prevalence and demographic pattern of patients with KS seen at the CMJAH dermatology outpatient clinic during the period of December 2004 to December 2019 (post ARV rollout on 1 April 2004). Methods: A retrospective record review of patients with a confirmed histological diagnosis of KS who attended the CMJAH from December 2004 to December 2019. CD4 count, viral load were compared throughout the study period.2 significant time frames were also compared during the study (2009 and 2010) And (2014 and 2015), which were the periods when ARV initiation protocols were adjusted in South African by WHO. The Kruskal Wallis analytic test was used. Results: 878 patients were enrolled into the study, with the majority being males (57% with n=499) and females (47% with n=379) .The mean age was 37,85 with a Standard Deviation of 10,29. The most affected age group range was between 30 to 49 years. The comparison of CD4 counts between KS patients from 2004 to 2019 did not show any statistical significance as the p value was 0, 424. The highest mean value of CD4 count was 373 and lowest was 90.P<0,05 for viral load equated to a statistically significant difference in the viral load of KS patients after HAART introduction (2004 to 2019). The highest mean value of viral load was 430 253 and lowest was 399.2 significant time frames were also compared during the study (2009 and 2010) and (2014 and 2015), which were the periods when the ARV initiation protocols were adjusted by the WHO. Between 2009 and 2010, there was a 9% decrease in CD4 count numbers of KS patients in comparison to period between 2014 and 2015, which had a decrease of only 6% with introduction of new ARV regimen protocols. Within the same time frame, there were no statistically significant changes in the prevalence of KS as both p values were >0,05 with the period 2009 and 2010 p value of 0,486 and 2014 to 2015 p value of 0,808. Conclusion: Our study revealed a general surge in the frequency of KS cases, despite the initiation of HAART, with the highest number of cases being 112 in 2018. However the use of the Mann Whitney U test concluded that sex variation had no significant influence across gender when comparing the frequency of KS cases in both males and females to CD4 count and viral load. This was evidenced by a p value of 0,867 (for CD4 count) and 0,203 (for viral load) which were both greater than 0, 05
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Medicine in Dermatology, 2021